The Role of Gentle Parenting in Families to Prevent the Negative Impact of the Digital Era on Early Childhood - Sasmita, Ika; Zannatunnisya, Zannatunnisya (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The digital era that continues to develop today has a significant impact on children, especially young children. Uncontrolled use of gadgets can have negative impacts, such as impaired cognitive development, social interactions, excessive gadget addiction. Therefore, the role of parents in guiding and directing children in facing the digital era is very important. One parenting style that can be applied is gentle parenting, which emphasizes empathy, understanding, respect and boundaries. This approach aims to develop social emotional closeness and equip children to use technology wisely. This research aims to explore the role of gentle parenting in the family to prevent the negative impacts of the digital era on early childhood, using an approach based on empathy, respect, understanding and boundaries. This research method uses a qualitative method with a literature study approach, looking for journals, books or research that has been researched first. The results of this research show that parents with a gentle parenting style are very helpful in organizing and guiding children in using technology and facing the challenges of the digital era